2022
DOI: 10.3389/fnins.2022.860620
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the impact of suppression on visual acuity in children with amblyopia using a dichoptic visual acuity chart

Abstract: PurposeTo develop a novel dichoptic visual acuity chart that measures the impact of interocular suppression on the visual acuity of each eye when two eyes are open.MethodsFifty-four subjects (19 anisometropic amblyopia, 20 treated amblyopia, and 15 normal children) participated in this study. The visual acuity that was tested under dichoptic-optotypes condition (i.e., presented optotypes to the untested eye) was compared with that under monocular condition (i.e., cover the untested eye with opaque patch). Visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 46 publications
1
2
0
Order By: Relevance
“…Researchers, using specially designed dichoptic VA charts, showed that the amblyopic eye scored higher acuity when the fellow eye was occluded, but in binocular viewing conditions, it performed worse as a result of suppression from the dominant eye [17]. This effect was present in naive amblyopic and supposedly treated patients as well [17]. These findings support previous observations suggesting that amblyopia is indeed the result of binocular dysfunction.…”
Section: Pathogenesissupporting
confidence: 73%
See 2 more Smart Citations
“…Researchers, using specially designed dichoptic VA charts, showed that the amblyopic eye scored higher acuity when the fellow eye was occluded, but in binocular viewing conditions, it performed worse as a result of suppression from the dominant eye [17]. This effect was present in naive amblyopic and supposedly treated patients as well [17]. These findings support previous observations suggesting that amblyopia is indeed the result of binocular dysfunction.…”
Section: Pathogenesissupporting
confidence: 73%
“…This mechanism is referred to as suppression in favor of the dominant eye, causing the "weaker" eye to become amblyopic [14]. The depth of suppression is positively associated with the amount of VA reduction [14,17]. Researchers, using specially designed dichoptic VA charts, showed that the amblyopic eye scored higher acuity when the fellow eye was occluded, but in binocular viewing conditions, it performed worse as a result of suppression from the dominant eye [17].…”
Section: Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation